Protein acetylation in skeletal muscle mitochondria is involved in impaired fatty acid oxidation and exercise intolerance in heart failure. Issue 5 (30th August 2018) - Tsuda, Masaya; Fukushima, Arata; Matsumoto, Junichi; Takada, Shingo; Kakutani, Naoya; Nambu, Hideo; Yamanashi, Katsuma; Furihata, Takaaki; Yokota, Takashi; Okita, Koichi; Kinugawa, Shintaro; Anzai, Toshihisa
Abstract: Background: Exercise intolerance is a common clinical feature and is linked to poor prognosis in patients with heart failure (HF). Skeletal muscle dysfunction, including impaired energy metabolism in the skeletal muscle, is suspected to play a central role in this intolerance, but the underlying mechanisms remain elusive. Lysine acetylation, a recently identified post‐translational modification, has emerged as a major contributor to the derangement of mitochondrial metabolism. We thus investigated whether mitochondrial protein acetylation is associated with impaired skeletal muscle metabolism and lowered exercise capacity in both basic and clinical settings of HF. Methods: We first conducted a global metabolomic analysis to determine whether plasma acetyl‐lysine is a determinant factor for peak oxygen uptake (peak VO2 ) in HF patients. We then created a murine model of HF ( n = 11) or sham‐operated ( n = 11) mice with or without limited exercise capacity by ligating a coronary artery, and we tested the gastrocnemius tissues by using mass spectrometry‐based acetylomics. A causative relationship between acetylation and the activity of a metabolic enzyme was confirmed in in vitro studies. Results: The metabolomic analysis verified that acetyl‐lysine was the most relevant metabolite that was negatively correlated with peak VO2 (r = −0.81, P < 0.01). At 4 weeks post‐myocardial infarction HF, a treadmill test showed lowered work (distance × body weight) and peak VO2 in the HF mice compared with the sham‐operated mice (11 ± 1 vs. 23 ± 1 J, P < 0.01; 143 ± 5 vs. 159 ± 3 mL/kg/min, P = 0.01; respectively). As noted, the protein acetylation of gastrocnemius mitochondria was 48% greater in the HF mice than the sham‐operated mice ( P = 0.047). Acetylproteomics identified the mitochondrial enzymes involved in fatty acid β‐oxidation (FAO), the tricarboxylic acid cycle, and the electron transport chain as targets of acetylation. In parallel, the FAO enzyme (β‐hydroxyacyl CoA dehydrogenase) activity and fatty acid‐driven mitochondrial respiration were reduced in the HF mice. This alteration was associated with a decreased expression of mitochondrial deacetylase, Sirtuin 3, because silencing of Sirtuin 3 in cultured skeletal muscle cells resulted in increased mitochondrial acetylation and reduced β‐hydroxyacyl CoA dehydrogenase activity. Conclusions: Enhanced mitochondrial protein acetylation is associated with impaired FAO in skeletal muscle and reduced exercise capacity in HF. Our results indicate that lysine acetylation is a crucial mechanism underlying deranged skeletal muscle metabolism, suggesting that its modulation is a potential approach for exercise intolerance in HF.